Parents' Understanding of Fulfilling Balanced Nutrition in Preparing Lunch Boxes for Group B Children - Yemima Elza Yany Br Perangin-angin; Nice Maylani Asril S.Psi., M.Psi., P.Hd., Psikolog; Made Vina Arie Paramita S.Pd., M.Pd (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Nutritional problems become a complex problem for children. This study aims to provide an in-depth description and analysis of parents' understanding of fulfilling balanced nutrition through preparing lunch boxes for group B children. This type of research is a case study qualitative research. The subjects in this study were the school principal, homeroom teacher in class B-1, homeroom teacher in class B-2, and parents. Data collection in this study was carried out through observation, interviews, and documentation. Data analysis techniques use data triangulation techniques. Based on the results of data analysis, several findings were obtained in this study. First, the contents of the children's lunch box used healthy and nutritious food, but different from the balanced nutritional standards needed by children. Both parents' understanding of balanced nutrition is quite good. It can be seen in parents’ awareness of preparing their children's lunch. Third, the role of schools is very good in supporting the development and introduction of nutrition for parents and children. From these three findings, it can be concluded that children's lunch boxes contain healthy and nutritious food. It is related to the level of parents’ understanding and good support from schools regarding the development and introduction of nutrition for children.